P.094 Referral Practices for Epilepsy Surgery in Pediatric Patients: A North American Study. (November 2021) - Buttle, SG; Muir, K; Dehnoei, S; Webster, R; Tu, A
Abstract : Background: The International League Against Epilepsy recommends patients with drug resistant epilepsy (DRE) be referred for surgical evaluation, however prior literature suggests this is an underutilized intervention. This study captures practices of North American pediatric neurologists regarding the management of DRE and factors which may promote or limit referrals for epilepsy surgical evaluation. Methods: A REDCap survey distributed via the Child Neurology Society mailing list to pediatric neurologists practicing in North America. "R" was used to conduct data analyses. Ethics approval from the CHEO REB was granted prior to the start of data collection. Results: 102 pediatric neurologists responded, 77% of whom currently practice in the United States. 73% of respondents reported they would refer a patient for surgical consultation after two failed medications. Of all potential predictors tested in a logistic regression model, low referral volume was the only predictor of whether participants refer patients after more than three failed medications. Conclusions: Pediatric neurologists demonstrate fair knowledge of formal recommendations to refer patients for surgical evaluation after two failed medication trials. Other modifiable factors reported, especially family perceptions of epilepsy surgery, should be prioritized when developing tools to enhance effective referrals and increase utilization of epilepsy surgery in the management of pediatric DRE.